PENGARUH LAYANAN INFORMASI TERHADAP PEMANFAATAN PERPUSTAKAAN PADA SISWA SMA - Saber, Florentina Merry; Asrori, Muhamad; Wicaksono, Luhur (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractLibrary utilization is one of  types of various types library that very relation with learning in school and constitute wrong one media to support sustainability studying in school utilization of this library very take effect towards activity learners in working on task and search carefully utilization of the school library in the learning interpreted as something action which is conducted for take benefits of what which has provided by the library, including utilization collection ingredients library which in in library for interests learn as for formulation of the problem general  research This is how influence of service information  to library utilization in SMAN 2 Sungai Raya.that method used is method descriptive that is look  reality in the field as a matter of fact which exists and as is with form studies relationship and use approach quantitative that is procedure solving problem with describe distribution influence information service library utilization learners class XII SMAN 2 Sungai Raya.  While technique collection data used  in research this is communication techniques indirect collection tool data used in research This is questionnaire information service and questionnaire library utilization in school SMAN 2 Sungai Raya on stage implementation  reach  score 92% ?very good? its success supported with material which is given methods and media. Recitation material reach score 90%,  coaching method achieve score 90%  and media coaching achieve score 89%.Keywords: Information Services, Library Utilization